Literasi Keuangan Syariah Di SMPN 2 Kec. Bangkinang Kota - Zubaidah Assyifa; Mohd Winario; Wahyu Febri Ramadhan Sudirman; Nala Amalia; Nur Amelia (EL-EMIR INSTITUTE, 2026)
This community service activity was conducted at SMP Negeri 2 Bangkinang Kota, Kampar Regency, Riau Province. This activity aims to socialize basic knowledge about Islamic economics to students from an early age so that they have a good understanding of Islamic economic principles in everyday life. The material presented covered the basic concepts of Islamic economics, the importance of avoiding usury practices, and the application of the values ​​of justice and honesty in economic activities. The results of the activity indicate that the implementation of the community service went well and achieved the set targets. This success was evident in the achievement of the planned number of participants, the achievement of the activity objectives, the delivery of all materials according to plan, and the increased ability of participants to understand the material presented. Furthermore, participant enthusiasm throughout the activity was also very high. This was evident from the active participation of students in the discussion and question and answer sessions. The level of participant satisfaction was also quite good, as evidenced by their ability to answer the questions posed. This activity provided benefits in the form of increased student knowledge and understanding of Islamic economic principles and their application.